Evaluation of the role of the body's response to skin damage in the background of experimental alloxan diabetes. (Eurasian Medical Research Periodical, 2023)
Chemical models of diabetes occupy the first place in experimental diabetology. Modeling of artificial skin damage in alloxan-induced diabetes, assessment of skin defect recovery, and the use of products developed on the basis of Bombyx mori fibroin for pharmacological repair of wounds, a comparative study of the regeneration process of skin wounds based on the typological response of animals